Comparison of dermatosis acne vulgaris in obese and non-obese patients - Qasim, Malik Muhammad; khan, Muhammad Sikander Ghsyas; Agha, Qasima; Sikander, Madiha; Agha, Farida; Sultana, Azima (Journal of Fatima Jinnah Medical University, 2023)
Background: Obesity is a disorder characterized by increase fat deposition in human body. Acne vulgaris is a common skin disease, affecting approximately 9.4% of the world’s population, with considerable effect on the quality of life. According to a previously conducted study, the prevalence rate of acne in Pakistan was found to be 5%. Obesity is increasing rapidly in developed and developing world. Acne vulgaris is commonly associated with obesity. The objective of this study is to compare the acne vulgaris in obese and non-obese patients. Patients and methods: It was a cross-sectional descriptive survey in which 300 obese and 300 non-obese patients were included respectively. Dermatosis, acne vulgaris was observed in the patients selected through inclusion criteria. This study was conducted in The University of Lahore Pakistan. Data was collected from outdoor Patients of skin Department of The University of Lahore Hospital during April 2020 to October 2020, by using questionnaire. Consent was taken before data collection. Data was analyzed through SPSS version 20. Results: Mean age of obese group was 37.4±13.0 years and non obese group was 30.9±15.6 years. In obese group 161(53.7%) were females, while 139(46.3%) were males respectively. In non-obese patients 193(64.3%) were males and 107(35.7%) were females respectively. In obese group, 115 (38.3%) had acne vulgaris, while in non-obese group 41 (13.7%) were affected with acne (P value ˂ 0.05). Conclusion: It is concluded that dermatosis acne vulgaris is significantly greater in obese patients as compared to non-obese patients. Obese persons should be given special consideration in terms of proper referral and management.